DNA, histones and neutrophil extracellular traps exert anti-fibrinolytic effects in a plasma environment - Varjú, Imre; Longstaff, Colin; Szabó, László; Farkas, Ádám Zoltán; Varga-Szabó, Veronika Judit; Tanka-Salamon, Anna; Machovich, Raymund; Kolev, Krasimir (Thrombosis and Haemostasis, 2015)
In response to various inflammatory stimuli, neutrophils secrete neutrophil extracellular traps (NETs), web-like meshworks of DNA, histones and granular components forming supplementary scaffolds in venous and arterial thrombi. Isolated DNA and histones are known to promote thrombus formation and render fibrin clots more resistant to mechanical forces and tissue-type plasminogen activator (tPA)-induced enzymatic digestion. The present study extends our earlier observations to a physiologically more relevant environment including plasma clots and NET-forming neutrophils. A range of techniques was employed including imaging (scanning electron microscopy (SEM), confocal laser microscopy, and photoscanning of macroscopic lysis fronts), clot permeability measurements, turbidimetric lysis and enzyme inactivation assays. Addition of DNA and histones increased the median fibre diameter of plasma clots formed with 16 nM thrombin from 108 to 121 and 119 nm, respectively, and decreased their permeability constant from 6.4 to 3.1 and 3.7×10−9 cm2. Histones effectively protected thrombin from antithrombin-induced inactivation, while DNA inhibited plasminogen activation on the surface of plasma clots and their plasmin-induced resolution by 20 and 40 %, respectively. DNA and histones, as well as NETs secreted by phorbol-myristate-acetate-activated neutrophils, slowed down the tPA-driven lysis of plasma clots and the latter effect could be reversed by the addition of DNase (streptodornase). SEM images taken after complete digestion of fibrin in NET-containing plasma clots evidenced retained NET scaffold that was absent in DNase-treated clots. Our results show that DNA and histones alter the fibrin architecture in plasma clots, while NETs contribute to a decreased lytic susceptibility that can be overcome by DNase.
Keywords: Neutrophil extracellular traps; DNA; histones; fibrinolysis; plasmin